Avaliação da produção de sedimentos em estradas não pavimentadas com diferentes níveis de uso - D'Ávila, Wilson Pimenta da Silva (2013)
Assessing sediment yield in unpaved roads is extremely important because they are considered significant sources of sediment, even though they are not much monitored in Brazil. Studies have shown that road maintenance provides several particles that are transported through surface runoff. In order to quantify sediment yield in unpaved roads, it is necessary to adopt monitoring techniques that assess coarse and fine particles separately. This study aims at assessing sediment yield in unpaved roads with different levels of use, in order to contribute to better understand the effects of road maintenance in sediment yield, as well as testing a monitoring technique to quantify coarse and fine particles separately. The equipment adopted was a retention tank for coarse sediments, attached to two tilting chambers to quantify flow rate; and a strategy to sample suspended sediments. The device was assembled at two sections of roads located in the municipality of Santa Teresa, ES, Brazil, where monitoring was carried out between Sept. 15, 2012 and March 15, 2013. Twenty-five (25) rainfall events were recorded in this period. The two sections monitored, one more and the other less frequently used, yielded on average 93.3 g m-2 and 9.7g m-2, respectively. Of these, 68% and 32% corresponded to the load of suspended sediments, in the section that was more and the one that was less used, respectively. Sediment yield showed significant correlation with rainfall erosivity, volume and surface runoff flow in both sections monitored. Also, it was estimated at 4.59 kg m-2 year-1 and 0.36 kg m-2 year-1 in the sections more and less frequently used, respectively. The section that was most frequently used showed higher flow rate and surface runoff volume. Because of the large amounts of particles available as a result of road maintenance, it showed sediment yield almost ten times higher than the less frequently used road section. The monitoring technique adopted was considered to be adequate to quantify coarse and fine particles separately